Characterization of unilateral conjunctival inoculation with Mycoplasma gallisepticum in house finches. Issue 5 (3rd September 2018) - Hawley, Dana M.; Moyers, Sahnzi C.; Caceres, Johanel; Youngbar, Courtney; Adelman, James S.
ABSTRACT: House finches in much of the continental United States experience annual epidemics of mycoplasmal conjunctivitis, caused by the bacterial pathogen Mycoplasma gallisepticum (MG). Although evidence suggests that natural infections typically begin unilaterally, experimental inoculations of songbirds with MG to date have all been administered bilaterally. Furthermore, studies of free-living finches find more severe clinical signs of mycoplasmal conjunctivitis in left versus right eyes, but the mechanisms underlying this side bias remain unknown. Here, we characterized unilateral inoculation of house finches with MG, and tested whether differential susceptibility of left versus right conjunctiva explains the side bias in disease severity of free-living finches. We directly inoculated house finches in either the left or right conjunctiva and characterized resulting disease severity and pathogen load throughout the course of infection. As expected, unilateral inoculation resulted in significantly more severe conjunctivitis, as well as higher conjunctival bacterial loads, on whichever side (left or right) birds were directly inoculated. However, in 55% of cases, unilateral inoculations resulted in bilateral disease, and in 85% cases there was evidence of bilateral infection. The overall severity of disease did not differ for birds inoculated in the left versus right conjunctiva, suggesting that physiological differences between the conjunctivae cannot explain the side bias in disease severity of free-living birds. Instead, laterality in exposure, perhaps due to feeding handedness, likely explains the detected field patterns. RESEARCH HIGHLIGHTS House finches show more severe disease in the directly inoculated conjunctiva. Unilateral inoculations lead to high rates of bilateral infection and disease. Overall disease severity does not differ for the left- or right-inoculated conjunctiva. Laterality in exposure likely explains the left-side bias in natural infections.